Predictors of depression among trainee counselors: the role of coping styles and resilience - Ying, Ng Jia; Engku Kamarudin, Engku Mardiah; Afdal; Shafie, Amin Al Haadi (Universiti Putra Malaysia, 2024)
Training to become a counselor is a uniquely challenging process, and trainee counselors report depressive symptoms, although most are not diagnosed with mental illness. This study investigates whether coping strategies and resilience predict depression among trainee counselors. The sample consisted of 182 participants, all enrolled as trainee counselor students at public universities in Malaysia. Remarkably, within this study, 46.2% of trainee counselors were found to be grappling with moderate to severe depressive symptoms. The study brings to light significant associations among trainee counselors between coping mechanisms, such as emotion-focused and avoidant coping, resilience, and depression. Nevertheless, only avoidant coping and resilience emerged as robust predictors of depressive symptoms. These findings underscore the heightened vulnerability of trainee counselors to the development of depressive symptoms, emphasizing the potential benefit of addressing avoidant coping strategies to alleviate these symptoms. Furthermore, these results underscore the critical significance of nurturing resilience and fostering positive coping skills among counselor trainees, especially those exhibiting heightened levels of depressive symptoms.